Characterization and ethanol fermentation of Pichia and Torulaspora strains - Rumpa Jutakanoke, Somboon Tanasupawat, Ancharida Akaracharanya (Journal of Applied Pharmaceutical Science, 2014)
Seventy-two yeasts were isolated from sugarcane juices and sugar process-sediments collected in Thailand by incubated at 30 and 40oC in oxygen-limited condition. Six and eleven isolated yeasts produced ethanol with 0.46 and 0.22 g/g initial glucose at 30 and 40oC, respectively. The highest ethanol production efficacy, 0.30 g/g glucose of maximum ethanol yield at 40oC was found in isolates G1-4(1) and G1-12(3). On the basis of their phenotypic characteristics including the D1/D2 region of the large-subunit ribosomal (LSU) of 26S rRNA gene sequence analysis, the isolates G1-4(1) and G1-12(3) were identified as Pichia kudriavzvii and Torulaspora globosa, respectively.
Keywords: Ethanol, yeast, Pichia kudriavzvii, Torulaspora globosa.